ADVANCES IN DIAGNOSIS AND TREATMENT OF HEMORRHAGIC STROKE IN THE PEDIATRIC POPULATION - Khakimov M.N. (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: Recent advances in neuroimaging, critical care, and surgical techniques have significantly improved the diagnosis and treatment of hemorrhagic stroke in children. However, challenges remain in early recognition and long-term management. This article reviews modern diagnostic tools, treatment strategies, and emerging therapies for pediatric hemorrhagic stroke.